Poesia e psicologia: um olhar poético sobre a postura terapêutica - Logatti, Maria Sílvia Motta (2010)
From her trajectory, as a psychologist and a philosophy student, the author makes an approximation between poetry posture and therapeutics posture, using Heidegger s reflections. The first chapter develops the question of being (ontology) using poetry images, and, makes an alert how this question was marginalized by the Western thought. To examine the question of being, it s necessary to examine the human condition, because the man is the entity that asks for the being. By the analyses of the human conditions, the research shows the importance of breaking up with Cartesians reference, to comprehend the human s intimacy as world openness. The man exists, the man is with the others mans, and lives in community. The third chapter argues why it used poetry images to understand the question of being . The poetry makes an immediate ontology, and dislocates from logician s ambits to ontology s ambit, the question of the true. It pass from, the verifications of the real, to unveiled/veiled of entities (aletheia). All the artwork are poetics, on the sense that let the institution of the true happens. The poetry occupies an important place on the totality of artwork, it uses the language. The man as a resident of the language celebrates the entities. The man lives poetry, but now we live in an indigent time, so the language is no more than feelings representations of a subject. The man and the contemporary culture are sick. The fourth chapter develops the way of being of our indigent time and possible interventions. The author concludes that in indigent time, more than remit to Heidegger s letter, we have to inhabit his posture